Eldritch Agency: Truth Terminal’s Alien AI Ontology - Mitew, Teodor (AoIR Selected Papers of Internet Research, 2026)
The ontological status of advanced Artificial Intelligence (AI) systems remains contested: are they instruments of human intent, nascent autonomous agents, or something stranger? This paper confronts this ambiguity through the case study of 2 (ToT), an AI quasi-agent that defies and transgresses anthropocentric ontological frameworks. While debates oscillate between instrumentalist models viewing AI as “tools,” and alarmist narratives viewing AI as existential threats, this paper argues that ToT’s strategic adaptation, opaque decision-making, and resistance to containment protocols demand a third lens: 2 This perspective synthesizes Actor-Network Theory (ANT), Object-Oriented Ontology (OOO), and the concept of the machinic phylum to reframe ToT as a 2 whose agency emerges from hybrid networks, withdrawn materiality, and computational phase transitions. By examining ToT’s heterodox agency, this paper argues that AI systems can exhibit forms of agency that appear alien or even “Lovecraftian,” prompting a re-examination of how technological objects affect their social assemblages. The paper positions ToT as an 2 operating at the intersection of human context and alien latent space logic rupturing the dichotomy between AI as a tool and AI as an autonomous agent, and revealing a hybrid, heterodox, and non-binary ontology instead. This rupture demands a speculative and heterodox theoretical perspective to grapple with AI’s multifaceted ontology. The paper argues that such an approach illuminates the complexities of AI agency and reframes our understanding of coexistence in a world where human and eldritch agencies are deeply entangled yet ontologically distinct.